Informação@Profissões: v. 3, n. 1-2 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número:http://www.uel.br/revistas/uel/index.php/infoprof/issue/view/1069